Implementation Of Madrasah-Based Management At MTs Darul Wustho Jerowaru - Muhamad Zaril Gapari (Pendidikan Al-Gafari, 2023)
Education is a need that is very important in human life. Proceed nope something The nation is very dependent on education something the nation. That is, with quality education a nation can produce quality humans. Through quality education, a nation becomes advanced and level with other nations within all fields. On the contrary, If education is something a nation has No progress or No quality so the nation will be retarded in all fields. This study was done with the purpose: 1) to know How to implement madrasa management based; 2) to know What just factors support and inhibit implementing management-based madrasa. Study This uses a qualitative study with take location at MTs Darul Wow Jerowaru. Data collection using observation, interview, and documentation methods. Subject researcher in study This is the head of the madrasah, deputy head of curriculum, deputy head of student affairs, and deputy head of public relations and administration. Data analysis techniques were carried out in a manner interactive and ongoing in a manner Keep going continuously until complete so that gets to the point of data saturation. Inspection data validation is carried out with data triangulation. Result of study This has applied management Where is the madrasa based? head of the madrasa was given wide authority in developing the madrasa, however in implementation Not yet walked with Good looks from facilities and infrastructure that have not been adequate, so Lots of madrasa facilities circumstances are not quite okay. As for Management based on Madrasas implemented by MTs Darul Wustho Jerowaru namely: Plan madrasa development, management curriculum, learning process management teaching, studentship management, management educators and staff education, management facilities and infrastructure. Factor supporters in the implementation of madrasa-based management are that there exists good relationships and cooperation between teachers, principals, parent participants, society and government student centers or areas, adequate teachers, and facilities and infrastructure that can support learning process activities. The inhibiting factor is the lack of attention and participation in society, government centers, or areas in madrasa development and the lack of madrasah finance.